Noninvasive and minimally invasive techniques for the diagnosis and management of allergic diseases. Issue 4 (11th April 2021) - Baumann, Ralf; Untersmayr, Eva; Zissler, Ulrich M.; Eyerich, Stefanie; Adcock, Ian M.; Brockow, Knut; Biedermann, Tilo; Ollert, Markus; Chaker, Adam M.; Pfaar, Oliver; Garn, Holger; Thwaites, Ryan S.; et al.
Abstract: Allergic diseases of the (upper and lower) airways, the skin and the gastrointestinal tract, are on the rise, resulting in impaired quality of life, decreased productivity, and increased healthcare costs. As allergic diseases are mostly tissue‐specific, local sampling methods for respective biomarkers offer the potential for increased sensitivity and specificity. Additionally, local sampling using noninvasive or minimally invasive methods can be cost‐effective and well tolerated, which may even be suitable for primary or home care sampling. Non‐ or minimally invasive local sampling and diagnostics may enable a more thorough endotyping, may help to avoid under‐ or overdiagnosis, and may provide the possibility to approach precision prevention, due to early diagnosis of these local diseases even before they get systemically manifested and detectable. At the same time, dried blood samples may help to facilitate minimal‐invasive primary or home care sampling for classical systemic diagnostic approaches. This EAACI position paper contains a thorough review of the various technologies in allergy diagnosis available on the market, which analytes or biomarkers are employed, and which samples or matrices can be used. Based on this assessment, EAACI position is to drive these developments to efficiently identify allergy and possibly later also viral epidemics and take advantage of comprehensive knowledge to initiate preventions and treatments.